Complications Associated with Emergency Obstetric Hysterectomy: A two year review at Lahore General Hospital, Lahore - Lubna Aslam, Nudrat Soail, Nazia Ayyub, Aiyza Sarwar, Azher Abbas Shah, Mehreen Gul (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Emergency obstetric hysterectomy is removal of the uterus to stop life threatening obstetric hemorrhage when all other measures fail. The life threatening hemorrhage and unavoidable emergency removal of the uterus is associated with considerable morbidity and mortality. Aim: To review the complications associated with the potentially avoidable procedure of EOH. Methods: All the women, regardless of booking status, presenting in emergency labor room and OPD of Gynae Unit 3 from January 2020 to December 2021, who underwent EOH were included in the study. Preventive measures and complications associated with the EOH were reviewed. Results: Total number of births recorded in two years, between January 2020 and December 2021 were 6809. Out of these, vaginal deliveries were 3669 (53.8%) and remaining were the Caesarean sections, 3140 (46.1%). Out of 48 EOH performed, majority of the complications (61.5%) encountered were hypovolemic shock, coagulopathy, re-exploration, and visceral injuries, each being 15.38% of the complications. Conclusion: EOH being the life-saving surgical procedure is associated with significant complications. Improving the antenatal care and health education of women can reduce the maternal morbidity and mortality especially in the developing countries.